(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article presents the results of research on the improvement of technological processes of reception, transportation and storage of cocoons. Technologies of filling the inner space of cocoons with technological water, their modern condition, and the results of research work on their improvement were also analyzed. A new form of device for receiving, transporting and storing cocoons was created and tested. In order to fill the inner cavity of the cocoons with technological water, a universal vacuuming equipment was created and tested in production conditions. The use of improved methods in the production allows to significantly improve the quality indicators of the received raw silk.